The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/3182387
|View full text |Cite
|
Sign up to set email alerts
|

Planning and Design of Equitable Free-Floating Bike-Sharing Systems Implementing a Road Pricing Strategy

Abstract: Promoting a more sustainable development of urban realities is one of the most important goals of the recent decades. One possible strategy to undertake in order to achieve this objective is the implementation of a road pricing: tolling private cars when passing by certain roads of the network could be a way to tone down the traffic congestion and, at the same time, encourage the shifting towards more sustainable means of transport. In this context, we suggest a method to distribute in a fair way the outcomes/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…There are only two state-of-the-art papers related to the location of virtual stations of FFBSSs. Caggiani et al [7] proposed a strategic designing methodology of FFBSSs whose facilities could be allocated in the territory according to spatial and social equity principles. Leonardo et al [5] proposed a dynamic and operator-based bike redistribution methodology that starts from the prediction of the number and position of bikes over an FFBSSs operating area and ends with a decision support system for the relocation process.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only two state-of-the-art papers related to the location of virtual stations of FFBSSs. Caggiani et al [7] proposed a strategic designing methodology of FFBSSs whose facilities could be allocated in the territory according to spatial and social equity principles. Leonardo et al [5] proposed a dynamic and operator-based bike redistribution methodology that starts from the prediction of the number and position of bikes over an FFBSSs operating area and ends with a decision support system for the relocation process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two recent studies have demonstrated the advances of FFBSSs. Caggiani et al [7] proposed a novel method for the strategic design of FFBSSs whose facilities could be allocated in the territory according to spatial and social equity principles. Leonardo et al [5] proposed a dynamic and operator-based bike redistribution method that could pursue a decision-making process for the relocation of FFBSSs operating area by predicting the number and position of shared bikes.…”
Section: Introductionmentioning
confidence: 99%
“…Pal et al [3] developed a "hybrid nested large neighbourhood search with variable neighbourhood descent algorithm" to solve the static rebalancing problems for both FFBS and public bicycles. Caggiani et al [25] aimed to optimize the FFBS allocation through test and real cases, according to spatial and social equity principles as well as the relationship of the toll amount, the days after policy applied and the pursued equity.…”
Section: Limited Research On Ffbsmentioning
confidence: 99%
“…Reiss and Bogenberger [23] created a demand model to obtain an optimal distribution of bikes within the operating area, based on a detailed GPS-data analysis for the bike-sharing system. Caggiani et al [24] suggested a method to use the revenue collected by a congestion price policy to implement a bike-sharing system. Pal and Zhang [25] proposed a hybrid nested large neighborhood search with variable neighborhood descent algorithm, which can solve static rebalancing problems for bike-sharing system.…”
Section: Literature Reviewmentioning
confidence: 99%